Subverted bodies: Scenic arts and memory in the 21st century. The Argentinian case (2020)
This article presents a critical journey through the constructions of memory regarding recent history developed in Argentinian theater in the first decades of the 21st century. To this end, an internal periodization and a diachronic analysis were proposed, focused on the study of paradigmatic cases which starts during the years prior to the beginning of the century to situate the relationships among scenic practices, politics, and memory, in each moment. As it is possible to suspect, in these decades, that scenic memories have brought into play the most diverse aesthetic language and have employed different ways of influencing the socio-political space, which will be particularized and specifically analyzed. At the same time, this panorama of the relationship between the scenic arts and constructions of memory in Argentina will, doubtlessly, allow links to be established with other countries of the region, particularly, in the Southern Cone.